Recent advances in the progress of immune checkpoint inhibitors in the treatment of advanced gastric cancer: A review - Shen, Jingjing; Wang, Zhongming (Frontiers in Oncology, 2022)
Most patients with advanced gastric cancer were treated with palliative therapy, which had poor curative effect and short survival time. In recent years, the clinical research of immune checkpoint inhibitors in advanced gastric cancer has made a breakthrough, and has become an important treatment for advanced gastric cancer. The mode of immune checkpoint inhibitors in the treatment of advanced gastric cancer includes single drug, combined chemotherapy, radiotherapy and multi-immunodrug combination therapy, among which combination therapy shows better clinical efficacy, and a large number of trials are currently exploring more effective combination therapy programs. In this paper, the new clinical research progress of immune checkpoint inhibitors in the treatment of advanced gastric cancer is reviewed, with emphasis on combination therapy.